A generalized Schwarz lemma for two domains related to μ-synthesis - Pal Sourav (De Gruyter, 2018)
We present a set of necessary and sufficient conditions that provides a Schwarz lemma for the tetrablock E. As an application of this result, we obtain a Schwarz lemma for the symmetrized bidisc G2. In either case, our results generalize all previous results in this direction for E and G2.